Pemanfaatan Sampah Organik Rumah Tangga untuk Produksi Pupuk Organik dalam Meningkatkan Ketahanan Ekonomi Keluarga - Prasetya, Muhammmad Roky; Prasetyo, Agus; Putri, Des Gita Adinda; Ananda, Dea Try; Sari, Yerni Puspita; Wagini, Wagini; Putri, Yesi; Susanti, Neri (Universitas Dehasen Bengkulu, 2025)
This community service program was carried out in RT 24 RW 4, Pematang Gubernur Subdistrict, Bengkulu City, with the objective of empowering local residents in managing household organic waste through the production of eco-enzyme and the use of a stacked-bucket biocompost reactor. The initiative began with field observations, followed by the construction of a biocompost reactor a week before the main training session. The socialization event took place at the residence of the RT head, was attended by local citizens, and featured a resource person from Yayasan Sehati Bengkulu. During the activity, participants learned directly how to make eco-enzyme using kitchen waste and how to operate a simple compost reactor made from used plastic buckets. Although the final results of the organic fertilizer were not yet visible due to the fermentation process requiring a longer time, the activity successfully increased residents’ awareness, participation, and understanding. This program highlighted that managing organic waste at the household level using simple and low-cost tools can contribute to environmental sustainability and economic resilience for families by enabling self-production of fertilizers.